Effectiveness of Early Literacy Activities for Anti-Bullying Education in Early Childhood: A Systematic Review - Alif Estiq Faroh; Tatminingsih, Sri; Budi Maryatun, Ika; Siti Syarah, Erie (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Bullying in early childhood poses significant long-term risks to children’s social and emotional development. Preventive efforts through early literacy activities have increasingly been recognized as an effective strategy to cultivate empathy, moral understanding, and social skills from an early age. This study aims to systematically review the literature on the effectiveness of early literacy activities in anti-bullying education for young children. The search process was conducted using three major electronic journal databases Google Scholar, JSTOR, and EBSCO employing standardized keywords. Article selection followed the PRISMA stages of identification, screening, eligibility, and inclusion, resulting in 15 studies that met the criteria. Findings indicate that activities such as storytelling, role-playing, and shared reading consistently enhance children’s understanding of empathy, emotional regulation, assertive communication, and prosocial behavior—core competencies essential for bullying prevention. Furthermore, early literacy activities strengthen positive social interactions through structured narratives and interpersonal simulations. Therefore, early literacy can be recommended as an effective pedagogical approach within early childhood curricula to support anti-bullying education through engaging and developmentally appropriate learning experiences.